Optimalisasi Peran Mahasiswa Fasilitator PUSPAGA dalam Layanan Publik Keluarga di RW 3 Manukan Wetan Surabaya - Widyastutik, Dwi Rahayu (TSAQOFAH, 2026)
This study aims to describe the optimization of the role of student facilitators of PUSPAGA in public family services at Balai RW 3, Kelurahan Manukan Wetan, Surabaya. The background of this research lies in the importance of the family as the primary environment for character formation and child protection, as well as the growing complexity of family problems in the city of Surabaya, which demands accessible accompaniment services. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings show that the role of students as facilitators has been optimized through counseling, consultation, referral services, parenting classes, and the implementation of the Puspaga Goes to School and Goes to Community programs. Students play an active role in assisting community members in accessing family services easily and free of charge. However, optimization is still constrained by low community participation and the limited multifunctional space available for service delivery. Overall, the program has operated reasonably well and has had a positive impact on improving literacy and family resilience at the neighborhood (RW) level, while also underscoring the importance of strengthening facilitator capacity and institutional support for the sustainability of community-based family services.